Carga percibida por los cuidadores de pacientes con discapacidades del Centro de Atención Terapéutica Especializado para Personas con Discapacidad (CATEPED) – Ibarra - Ayovi Valencia, Nelsi Nedelka (2024)
The objective of this research was to measure the perception of overload presented by caregivers of people with disabilities in the specialized therapeutic care center for people with disabilities (CATEPED), in the province of Ibarra in the period April-August 2024, the The research was descriptive and cross-sectional, with a quantitative approach where the state variable was not manipulated. The population included in this research was made up of 40 caregivers, where 68% were female housewives who did not meet the requirements. necessary resources to leave the care of their family member to another person, and 33% were men who distributed their time to leave the care of a family member or friend, to dedicate time to work and thus cover their household expenses, Participation was free and voluntary, where informed consent was given, where each caregiver gave a reading, and if they wished they could withdraw at any time during the research. The instrument used in the research was the Zarit test, which is A validated and safe tool worldwide designed specifically to measure the degrees of relative overload of caregivers of people with disabilities, this test measures financial, social, physical and psychological well-being, among others. In the research carried out, the result was that 73% of caregivers affirm that they do not experience a degree of burden when caring for their family member, while 28% affirm that they do.